Towards an understanding of digital marketing adoption among the retail sector: An analysis of small independent apparel retailers - MBIADJO FANDIO , Faustine Mimosette (Revue Internationale du Chercheur, 2024)
Digital technology provides new communication and distribution channels for consumers and suppliers in the retailing environment. Digital marketing enables retailers to attract, inform and communicate with their customers through its various tools. However, in Cameroon, the adoption of digital marketing in the retail sector is slow. In light of this, the present study aimed to analyse the various factors influencing implementing digital marketing strategies among small independent retailers when developing effective communication strategies. A sample of 538 small independent apparel retailers participated in the study, responding to a self-administered questionnaire. The findings obtained through descriptive analysis and logistic regression analysis led to the completion of the study’s objectives. As a result, it is possible to note that digital marketing is increasingly used by small apparel retailers in their communication with both customers and partners (suppliers). Social media is the most used tool in view of their wider audience. Moreover, the main reasons for the adoption of digital marketing are related to his profitability, to a better relationship with the consumers and the audience coverage. Furthermore, the main factors behind this adoption are facilitating conditions, customer pressure, employee skills, and competitive pressure.